Integrating quantitative and qualitative sources in drought impact assesment - Do Ó A. (Drought management: scientific and technological innovations, 2008)
One of the main specificities of droughts is that their impacts are non-structural, disseminated in time and space over various components of the water cycle, and affecting different human activities. Such features cause significant difficulties in quantifying economic losses and integrating impacts in different sectors, calling for a combined use of both quantitative and qualitative data sources. In this paper, the impacts of the 2004-06 drought event in the Algarve (South Portugal) are assessed, using a combination of statistics, reports, news and other sources, thus providing an integrated framework to drought impact assessment.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)